ANALYSIS OF EQUALITY IN SOCIAL, ECONOMIC AND EDUCATION IN ENGGELAM VILLAGE MUARA WIS , DISTRICT OF KUTAIKARTANEGARA - Futum Hubaib (Sosiohumaniora, 2020)
The background of this research is to look at and examine conditions, the community population around and in several  Enggelam villages  visited by the author, with a considerable amount of, social ,economic and education status of our society which is still below the welfare standard. The purpose of this research is to examine the causes and how solutions must be taken by the government, or the community itself, so that they can live in harmony with other communities whose lives, education in accordance with living standards. In this study the authors used a qualitative perspective method approach with a case study model, because the authors considered the qualitative method in accordance with the research conducted by the author. When this study was conducted the author examined 10 people as participants, to be informants in taking research data, and the time of the study conducted by the author was around 14 weeks. The results of this study the authors have found five indicators that must be used as a standard, to implement equality in education, social status and economy in society. Indicators that the authors the consider  (novelty) in the findings of this study .